Poverty and children's adjustment - Luthar, Suniya S. (Thousand Oaks, Calif. : Sage Publications, 1999)
Poverty and Children's Adjustment gives an interdisciplinary perspective on the effects of poverty, lack of education, and other negative socioeconomic forces on children's development. This volume provides an in-depth review of the literature on psychopathology among children faced with sociodemographic disadvantage, as well as suggested directions for future research. Suniya S.
Luthar integrates findings of empirical research, conducted over the past three decades, on processes implicated in the adjustment to socioeconomic deprivation.
1. Introduction -- 2. Child Attributes. Gender Differences in Vulnerability to Familial Stressors. Gender Differences in Vulnerability to Community-Related Influences. Age Differences. Personal Characteristics. Trajectories of Adjustment -- 3. Poverty and the Family: Demographic and Structural Features. Teenage Mothers. Family Structure. Ethnicity -- 4. Poverty and the Family: Psychological Processes. Poverty and Parents' Functioning. Parental Behaviors. Models of Family Functioning in the Context of Poverty -- 5. Exosystemic Influences. Support Networks. The Physical Environment. Neighborhoods. Violence in the Neighborhood -- 6. Future Directions. Childhood in Poverty: Directions for Future Inquiry. Interventions. Teaching and Curricula.
Includes bibliographical references (pages 95-114) and indexes.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Poor children -- United States -- Psychology; Children with social disabilities -- United States -- Psychology; Poverty -- United States -- Psychological aspects; Adjustment (Psychology) in children -- United States; Child psychopathology -- United States; Social adjustment; Adaptability (Psychology); Children; Poverty; Social Adjustment; Adaptation, Psychological; Child; Poverty; Enfants pauvres -- États-Unis -- Psychologie; Enfants socialement défavorisés -- États-Unis -- Psychologie; Pauvreté -- États-Unis -- Aspect psychologique; Ajustement chez l'enfant -- États-Unis.; Enfants -- Psychopathologie -- États-Unis.; Adaptation sociale; Adaptation (Psychologie); Enfants; Pauvreté.; children (people by age group); poverty; POLITICAL SCIENCE -- Public Policy -- Social Security; POLITICAL SCIENCE -- Public Policy -- Social Services & Welfare; Social adjustment; Children; Adaptability (Psychology); Adjustment (Psychology) in children; Child psychopathology; Children with social disabilities -- Psychology; Poor children -- Psychology; Poverty -- Psychological aspects; United States; Armut; Kind; Integration; Unterprivilegierung; USA